2003
DOI: 10.1128/jvi.77.15.8418-8425.2003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the α-2,6-Sialyltransferase in MDCK Cells Increases Influenza Virus Sensitivity to Neuraminidase Inhibitors

Abstract: No reliable cell culture assay is currently available for monitoring human influenza virus sensitivity to neuraminidase inhibitors (NAI). This can be explained by the observation that because of a low concentration of sialyl-␣2,6-galactose (Sia[␣2,6]Gal)-containing virus receptors in conventional cell lines, replication of human virus isolates shows little dependency on viral neuraminidase. To test whether overexpression of Sia(␣2,6)Gal moieties in cultured cells could make them suitable for testing human infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
306
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(332 citation statements)
references
References 35 publications
21
306
0
5
Order By: Relevance
“…Recent publications have reported on the expression of the human siat1 gene (ST6Gal I) in MDCK cells that was associated with an increase in ␣2,6-linked sialic acid on glycoproteins (29)(30)(31). The researchers wanted to increase the number of 6-linked sialic acids on the cell surface to enhance influenza virus sensitivity to neuraminidase inhibitor, which is the key component of antiviral drugs for influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported on the expression of the human siat1 gene (ST6Gal I) in MDCK cells that was associated with an increase in ␣2,6-linked sialic acid on glycoproteins (29)(30)(31). The researchers wanted to increase the number of 6-linked sialic acids on the cell surface to enhance influenza virus sensitivity to neuraminidase inhibitor, which is the key component of antiviral drugs for influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Madin-Darby canine kidney (MDCK) cells and human embryonic kidney cells transformed with large T antigen (293T cells) were obtained from the American Type Culture Collection (Manassas, VA). MDCK cells transfected with cDNA encoding human 2,6-sialyltransferase (MDCK-SIAT1 cells) were kindly provided by Mikhail N. Matrosovich and maintained as described previously (32,50).…”
Section: Methodsmentioning
confidence: 99%
“…To further evaluate the effect of the H274Y and N294S NA mutations on viral growth, we assayed the yields of the recombinant VN1203 (H5N1) and PR8 (H1N1) viruses after multiple replication cycles in MDCK cells (which exhibit more ␣-2,3-linked terminal sialic acid [SA] than ␣-2,6-linked terminal SA on the cell surface) and MDCK-SIAT1 cells (which exhibit more ␣-2,6-linked terminal SA than ␣-2,3-linked terminal SA on the cell surface) (32). At 12 hours …”
Section: Generation and In Vitro Characterizationmentioning
confidence: 99%
“…Previous studies have demonstrated that the functional balance between the receptor-binding HA activity and receptor-destroying NA activity of the surface influenza virus glycoproteins determines the pattern of emergence of NA inhibitor resistance (24,39,40). The disparate hemagglutinin (HA)-NA balance and the differences in sialic acid (SA) receptors between available continuous cell lines and human respiratory epithelial cells significantly limit the suitability of the commonly used cell cultures for phenotypic characterization of NA inhibitor resistance (21,24,39). Here, we used primary normal human bronchial epithelial (NHBE) cells, which possess human respiratory tract SA receptors; i.e., they express high concentrations of SA-␣2,6-galactose (Gal)-containing receptors and lesser amounts of SA-␣2,3-Gal receptors (22).…”
mentioning
confidence: 99%